Management of Splenic Abscess after Splenic Arterial Embolization in Severe Acute Pancreatitis: A 5-Year Single-Center Experience - Gang Li; Lin Gao; Jing Zhou; Bo Ye; Jingzhu Zhang; Cheng Qu; Lu Ke; Zhihui Tong; Weiqin Li (Gastroenterology Research and Practice)
Objective. To describe the management and prognosis of splenic abscess after splenic arterial embolization in severe acute pancreatitis (SAP) patients. Methods. This is a retrospective observational study. From August 2012 to August 2017, SAP patients with infected pancreatic necrosis (IPN) who underwent splenic arterial embolization after massive hemorrhage of the splenic artery were screened and those who developed splenic abscess were included for analysis. The demographic characteristics, etiology, treatment of splenic abscess, and clinical outcomes of these cases were collected and analyzed. Results. A total of 18 patients with splenic abscess formed after splenic arterial embolization were included for data analysis. The median age of the 18 patients was 46 years. The etiologies included biliary AP, hypertriglyceridemic AP (HTG-AP), and other causes. Ten patients underwent minimally invasive percutaneous drainage only for splenic abscess while the other eight patients received splenectomy. One patient died due to uncontrolled infection and another patient died due to massive bleeding, and the remaining sixteen patients survived. Conclusion. The incidence of splenic abscess was high in patients requiring splenic arterial embolization due to massive bleeding. Our data showed that most splenic abscess could be successfully managed with minimally invasive interventions, and traditional splenectomy should serve as a backup treatment.